How accession to the European Union has affected external trade and foreign direct investment in Central European economies - Kamiński, Bartłomiej 1944- (Policy research working paper, 2001)
During the Central European countries' reintegration into the world economy, their proximity and accession to the European Union greatly affected first the flow of capital and then the flow of goods. Countries that adopted radical liberal reform and had preferential access to EU markets have benefited most, attracting foreign direct investment and drawing multinational corporations relocating their production sites